Development and Validation of a New DIVA Real-Time PCR Allowing to Differentiate Wild-Type Lumpy Skin Disease Virus Strains, Including the Asian Recombinant Strains, from Neethling-Based Vaccine Strains - Andy Haegeman; Ilse De Leeuw; Wannes Philips; Nick De Regge (Viruses, 2023)
The current epidemic in Asia, driven by LSDV recombinants, poses difficulties to existing DIVA PCR tests, as these do not differentiate between homologous vaccine strains and the recombinant strains. We, therefore, developed and validated a new duplex real-time PCR capable of differentiating Neethling-based vaccine strains from classical and recombinant wild-type strains that are currently circulating in Asia. The DIVA potential of this new assay, seen in the in silico evaluation, was confirmed on samples from LSDV infected and vaccinated animals and on isolates of LSDV recombinants (n = 12), vaccine (n = 5), and classic wild-type strains (n = 6). No cross-reactivity or a-specificity with other capripox viruses was observed under field conditions in non-capripox viral stocks and negative animals. The high analytical sensitivity is translated into a high diagnostic specificity as more than 70 samples were all correctly detected with Ct values very similar to those of a published first-line pan capripox real-time PCR. Finally, the low inter- and intra-run variability observed shows that the new DIVA PCR is very robust which facilitates its implementation in the lab. All validation parameters that are mentioned above indicate the potential of the newly developed test as a promising diagnostic tool which could help to control the current LSDV epidemic in Asia.